Impacts of preharvest and postharvest handling and processing on bioactive compounds and functional properties of pomegranate fruit fractions and by-products - Mphahlele, Rebogile Ramaesele (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhD)--Stellenbosch University, 2016.